Carbon Pathway to Net Zero India’s Emissions By 2070 - Amareshagoud Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
As a signatory to the Paris Agreement, India has pledged to contribute to mitigating greenhouse gas emissions and building resilience against climate change. The country’s managing its responsibility under the national andinternationally determined contribution,through emission reduction policies, strategies, long-term policies and augmentation of carbon sinks to achieve net zero emissions by 2070, demonstrates India’s willingness to take climate action. The pathways for such action will be determined by the policy measures that the country adopts now and in the future.